7B.05: DIFFERENTIAL EFFECTS NEBIVOLOL AND VALSARTAN ALONE AND IN COMBINATION ON 24-HOUR AMBULATORY RATE-PRESSURE PRODUCT, STROKE LOAD, AND BLOOD PRESSURE-HEART RATE VARIABILITY. (June 2015) - Izzo, J.; Saleem, O.; Khan, S.; Osmond, P.
Abstract : Objective: Beta-blockers are antihypertensive drugs indicated for treatment of cardiomyopathies but little is known about their effects on cardiac workload in the ambulatory setting. We compared the effects of the beta-blocker nebivolol (N), the angiotensin receptor blocker valsartan (V) and combined V/N on 24-hour ambulatory central rate-pressure product (ACRPP, an index of myocardial oxygen consumption rate), stroke load (SL) and blood pressure-heart rate variability (SD and coefficient of variation). Design and method: Subjects with hypertension (SBP>140 or DBP>90, n = 26 including 21 blacks) were studied in a 3-way, double-blind, randomized crossover study. After 4 weeks of each drug (V 320, N 40, or V/N 320/40 mg daily), ambulatory pulse wave analysis (IEM MobilOGraph) was performed every 20 min for 24-hour with primary (ACRPP) and secondary endpoints analyzed by sequential paired t-analysis. SL = ACRPP/heart rate. Results: The table displays the main results. All 3 treatments resulted in similar brachial and central BP values. Addition of N to V resulted in lower ACRPP: 24-hour and daytime by 11 and 14% (p < 0.001 each) and nighttime by 4% (p < 0.02). This effect was driven largely by the heart-rate slowing effects of N (by 15–18%, p < 0.001 each). SL, however, was lower with V than either N or V/N (about 10%, p < 0.001 each). Variability (standard deviation and coefficient of variation) of ACRPP and heart rate were lower with N and V/N than V. Separate analysis of blacks revealed values very similar to those of the entire treatment group. Conclusions: We conclude that 24-hour ambulatory hemodynamic monitoring is feasible in clinical trials. The rate-slowing effects of nebivolol (both N and V/N) cause lower ambulatory cardiac oxygen consumption compared to V alone but at the same time, N and V/N cause an increase in stroke load. Absolute and relative heart rate variability is higher with V than N or V/N. These results are driven primarily by the effects in blacks. Figure. No caption available.